Carcinogenesis in prostate cancer: The role of long non-coding RNAs - John Aird; Anne-Marie Baird; Marvin C.J. Lim; Ray McDermott; Stephen P. Finn; Steven G. Gray (Non-coding RNA Research, 2018)
LncRNAs appear to play a considerable role in tumourigenesis through regulating key processes in cancer cells such as proliferative signalling, replicative immortality, invasion and metastasis, evasion of growth suppressors, induction of angiogenesis and resistance to apoptosis. LncRNAs have been reported to play a role in prostate cancer, particularly in regulating the androgen receptor signalling pathway. In this review article, we summarise the role of 34 lncRNAs in prostate cancer with a particular focus on their role in the androgen receptor signalling pathway and the epithelial to mesenchymal transition pathway.